The Effectiveness of the Implementation of the Mobile E-TLE System by Satlantas in Suppressing Traffic Violations in the Jurisdiction of Polres Boyolali (Advances in Police Science Research Journal, 2024)
Electronic Traffic Law Enforcement or commonly called E-TLE is a technology implementation program from the National Police Corps that is useful for recording various traffic violations electronically. However, in its implementation, the mobile ETLE program is still less effective in suppressing traffic violations. It is evident from the high number of traffic violations and traffic accidents. A qualitative approach was used in this study to gain an understanding of "The effectiveness of the implementation of the Mobile E-TLE system by Satlantas in suppressing traffic violations in the jurisdiction of Boyolali Police Station" both in the implementation by the Boyolali Police Traffic Unit and its effectiveness efforts. The type of research used is field research carried out by collecting information collected from research respondents through structured interviews The application of the Mobile E-TLE system, as a substitute for efforts to enforce traffic violations, so far has only been able to capture 3 types of traffic violations, which include not wearing a seat belt, not wearing a helmet, and over capacity for loaded vechile. Based on the findings obtained through research and discussion described in the previous chapter by linking existing factual and theoretical conditions, it is concluded that the implementation of the Mobile E-TLE system by the Boyolali Police Station has not been effective in suppressing traffic violations.
Keywords: Efektivitas, E-TLE Mobile, Pelanggaran Lalu Lintas, Satuan Lalu Lintas